Analisis Implementasi Pembelajaran Berdiferensiasi dalam Kurikulum Merdeka di SMAN 1 V Koto Kampung Dalam - Tami, Annisa Putri; Friyatmi, Friyatmi (Lembaga Yasin AlSys, 2023)
This study aims to analyze the implementation of differentiated learning in the independent curriculum at SMAN 1 V Koto Kampung Dalam along with its driving and inhibiting factors. This research is a quantitative descriptive research with a population of all teachers and grade X students in the 2023/2024 school year. The sample in this study amounted to 50 teachers and 159 students. Researchers took samples by means of probability sampling technique type proportionate random sampling. The data collection techniques used were questionnaires and interviews. The results showed that the factors that encourage the implementation of differentiated learning at SMAN 1 V Koto Kampung Dalam are the availability of teaching materials and teachers' understanding and experience with a percentage of 28% each. As for the inhibiting factors of the implementation of differentiated learning at SMAN 1 V Koto Kampung Dalam, the highest is the lack of teaching materials with a percentage of 39% and the understanding and experience of teachers with a percentage of 32%. Indirectly, the availability of teaching materials and teachers' understanding and experience can encourage and inhibit differentiated learning.